Penggunaan Proxy Untuk Bypass Region Lock Game Online (Studi Kasus Phantasy Star Online 2) - Ghafur, Muhammad Abdurahman; , Dr. Heru Supriyono, M.Sc (2015)
In the era of globalization, the internet needs an important role in everyday life. All kinds of information can be obtained easily and practically with the internet. Besides being a place of information, the Internet can also be a means of entertainment. One of them is online games. Not all online games can be enjoyed freely by every players in the world. Phantasy Star Online 2 server Japan (PSO2JP) is one example. The problem is that this game has a region lock. One commonly method is to bypass the region lock by using a proxy. By installing a proxy on the server, player can pass the blocking. Utilization of proxifier makes connection activity in and out of the proxy can be seen through by the log of proxifier. Proxy uses tunneling process whose task is to handle and provides a connection point-to-point from the source to its destination. Tunneling is encapsulation or wrapping a packet protocol in the protocol, so the request is made may pass through the region hitch lock and arrived at the destination.